EFL Pre-service Teacher Profile: A Level of Reflection Regarding Professionalism Readiness - Nur Cahya; Siti Suharsih; Murti Ayu Wijayanti; Suroso Mukti Leksono (Journal of English Language Teaching and Cultural Studies, 2024)
LPTK (Educational University) has a function and role in preparing professional prospective teachers. One of the indicators that must have is the ability to reflect on learning. The function of learning reflection has the aim of improving sustainable learning. the researcher would like to focus this study to find out how the level of reflection and to examine the level of reflection This research involve qualitative research, The data collection technique in this research is documentation of articles related to the research problem and the interview. The research instrument in this study is the reflection journal done by students when they have completed the learning. Then, the researcher conduct interviews with students regarding matters related to the results of the data.According to the results of the reflective learning journal worksheets conducted by EFL preservice teachers, there are (76.47%) at level C, (17.65%) at level D, and (5.88%) at level B. EFL preservice teachers unable to reach the highest level of reflection because a) Lack of understanding of reflective learning journals b) Difficulties getting to begin writing.This study concludes that the level of reflection level of EFL pre-service teachers are on average. Reflective learning journals need to be done regularly in every lesson to increase the level of reflection. Preparing professional EFL preservice teachers require a significant increase in the level of reflection.